Faktor risiko stunting pada anak umur 12-24 bulan - Wellina, Wiwien Fitrie; Kartasurya, Martha Irene; Rahfiludin, M. Zen (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background : In 2013, the prevalence of stunting and severe stunting in Brebes reached 26.9 % and 16.8 %. These prevalences of stunting were higher than the stunting prevlence in Central Java Province (11.0%). This study aimed to determine risk factors of stunting among children aged 12-24 months in Brebes District.Methods: This research was conducted with a case-control design on 77 cases (stunting) and 77 controls (normal) in Brebes Subdistrict. Data on birth weight, birth length, infection history, pesticide exposure were obtained through interviews, using structured questionnaires. The analysis was conducted by calculating Odd Ratios and logistic regressions.Results : Multivariate results showed that the risk factors of stunting in children aged 12-24 months in Brebes Â subdistrict were low energy adequacy levels (OR =7.71; 95%CI: 3.63-16.3; p=0.001), low protein adequacy levels (OR=7.65 ; 95%CI:3.67-15.9, p=0.001); low zinc adequacy levels (OR=8.78; 95%CI:3.53-21.5, p=0,001); low birth weight (OR=3.63; 95%CI:1.65-7.96; p=0.002) and high exposure to pesticides (OR=8.48; 95%CI:3.93-18.28; p=0,001). These three variables are contributing to stunting of 45 %. Low compliance of vitamin A capsule consumption, the frequencies of diarrhea respiratory infection were not the risk factors for stunting in this study.Conclusions: The risk factors of stunting among children aged 12-24 months were low energy adequacy levels, low protein adequacy levels, low zinc adequacy levels, low birth weight and high exposure to pesticides. The highest risk was the high pesticide exposure.